Deep Quality Cost Report Analysis Defective Product Control: Case Study of Maesan Bondowoso Black Crow Cigarette Company - Khoirul Liza Umamah; Norita Citra Yulinartati; Moh Halim (West Science Accounting and Finance, 2024)
The importance of quality costs for cigarette companies is to find out the extent to which the quality control system implemented by the company functions, if the lower the quality costs indicate the better the products produced by the cigarette company. The research uses a qualitative descriptive analysis method. Descriptive analysis was used to describe the variables in the research, while qualitative analysis was carried out to produce findings in the form of descriptions of research subjects and objects based on facts in field data obtained in research at the Maesan Bondowoso Black Crow Cigarette Company. based on research results, the Black Crow Cigarette Company, located in Pakuniran Village, Maesan District, Bondowoso Regency, East Java, was founded in 2004 by Mr. Nawar H. Wasıl. Basically, the company has implemented costs related to product quality, but the company has not specifically identified and categorized them. Therefore, the company should pay attention to costs that constitute quality and group these costs based on their classification.